2008
DOI: 10.2169/internalmedicine.47.0607
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Bone Marrow Dysplasia in Patients with Systemic Lupus Erythematosus

Abstract: Objective Several reports of bone marrow dysplasia in patients with systemic lupus erythematosus (SLE) Results Of the 17 SLE patients, 12 had dysplasias, including: erythroid cell multinuclearity (trinuclear or more) (5 patients), megaloblastoid changes (4), pseudo-Pelger abnormalities (6), annular nuclear myeloid cells (2), separated nuclear megakaryocytes (4), and micromegakaryocytes (5). In the 4 patients who had follow-up bone marrow aspiration

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…There is some evidence that BM may also be important in the pathogenesis of other autoimmune diseases such as chronic colitis and lupus 23 24. Certainly, BM is also a site for important pathology driving joint damage, and distinct subpopulations of mature lymphocytes present in BM from patients with RA and OA indicate that BM acts as an organ that actively contributes to the pathogenesis of RA.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that BM may also be important in the pathogenesis of other autoimmune diseases such as chronic colitis and lupus 23 24. Certainly, BM is also a site for important pathology driving joint damage, and distinct subpopulations of mature lymphocytes present in BM from patients with RA and OA indicate that BM acts as an organ that actively contributes to the pathogenesis of RA.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study by Oka et al, 6 17 patients with SLE were examined specifically for dysplasia. Erythroid, myeloid, and megakaryocytic dysplasia were all noted in patients with SLE and showed correlation with severity of disease.…”
Section: Quantitation Of Cell Lineages By Immunohistochemistrymentioning
confidence: 99%
“…Reports in the literature, including smaller studies mostly focused on either SLE or RA, show a variety of findings that lack a unifying theme. [4][5][6][7][8][9][10][11] As the etiologies of peripheral blood cytopenias are broad, and the findings are often nonspecific, bone marrow biopsies are often performed in cytopenic patients, especially to exclude both hematologic and nonhematologic malignancies. Once malignancies have been excluded, the differential diagnosis of other possible causes of cytopenias often remains broad and may require additional clinical information and laboratory testing.…”
mentioning
confidence: 99%
“…Oka et al found bone marrow dysplasia in all cell lineages in systemic lupus erythematosus (SLE) cases but the dysplasia was reversible during the course of the disease [17]. The hypothesis put forward regarding the hematopoietic dysplasia in SLE cases is related to higher hypercytokinemia (TNF-␣ and IFN-ϒ) inducing Fas upregulation with apoptosis of marrow CD34+ cells and abnormal hematopoiesis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest that cytokine alterations in ITP show major overlap with those of SLE and hence a similar mechanism may produce the appearance of microMKs in ITP [20,21]. Most studies indicate the absence of microMKs in control marrows with rare studies reporting as high as 5% microMKs in control marrow [17,22,23].…”
Section: Discussionmentioning
confidence: 99%